Mechanical properties of the gastrocnemius muscle‐tendon unit in male athletic high jumpers - Toshihide Fujimori; Natsuki Sado (Physiological Reports)
Abstract Tendon compliance facilitates power exertion during stretch‐shortening cycle exercises through muscle‐tendon interaction. Tendons stiffen in response to mechanical loadings, and their stiffness sometimes affects motor performance, but no consensus has been reached yet. We investigated the gastrocnemius muscle‐tendon properties of 10 male amateur high jumpers and 14 untrained males. Participants performed maximum voluntary contraction (MVC) of ankle plantar flexion. We measured the maximum joint torque and Achilles tendon stiffness using a torque dynamometer for force measurement, an ultrasound apparatus to track tendon elongation, and a motion capture system to correct joint rotation. High jumpers exerted significantly greater MVC torque than untrained individuals (152.8 ± 31.8 vs. 103.6 ± 18.9 Nm). Tendon stiffness did not significantly differ between groups (287.3 ± 90.9 vs. 258.4 ± 85.6 N/mm). This suggests that strengthening muscles and stiffening tendons may independently adapt through high jump training. In high jumpers, high jump personal best record significantly correlated with MVC torque (r = 0.73) but not significantly correlated with tendon stiffness (r = −0.07). Muscle force exertion ability enhanced by training should be important for improving high jump performance, while tendon stiffening is not necessary for performance. We suggest that humans may inherently have adequate tendon properties for jumping, even without specific training.